Quantum transport equations for Bose systems taking into account nonlinear hydrodynamic processes - Hlushak, P.A.; Tokarchuk, M.V. (Condensed Matter Physics, 2014)
Using the method of nonequilibrium statistical operator by Zubarev, an approach is proposed for the description of kinetics which takes into account the nonlinear hydrodynamic fluctuations for a quantum Bose system. Non-equilibrium statistical operator is presented which consistently describes both the kinetic and nonlinear hydrodynamic processes. Both a kinetic equation for the nonequilibrium one-particle distribution function and a generalized Fokker-Planck equation for nonequilibrium distribution function of hydrodynamic variables (densities of momentum, energy and particle number) are obtained. A structure function of hydrodynamic fluctuations in cumulant representation is calculated, which makes it possible to analyse the generalized Fokker-Planck equation in Gaussian and higher approximations of the dynamic correlations of hydrodynamic variables which is important in describing the quantum turbulent processes. Використовуючи метод нерiвноважного статистичного оператора Зубарєва, запропоновано пiдхiд для
опису кiнетики з врахуванням нелiнiйних гiдродинамiчних флуктуацiй для квантової бозе-системи. Розраховано нерiвноважний статистичний оператор, що узгоджено описує як кiнетичнi, так i нелiнiйнi гiдродинамiчнi процеси. Отримано кiнетичне рiвняння для нерiвноважної одночастинкової функцiї розподiлу
та узагальнене рiвняння Фоккера-Планка для гiдродинамiчних змiнних (густин iмпульсу, енергiї i кiлькостi частинок). В кумулянтному наближеннi розраховано структурну функцiю гiдродинамiчних флуктуацiй.
Це надає можливiсть проаналiзувати узагальнене рiвняння Фоккера-Планка в гаусовому i вищих наближеннях для динамiчних кореляцiй, що важливо для опису квантових турбулентних процесiв.